Distributed renewable energy integration using distribution locational marginal pricing and the food-energy-water nexus - Edmonds, Lawryn (Kansas State University, 2022)
An increase in distributed energy resources (DERs), particularly non-dispatchable variable renewable energy (VRE) sources such as rooftop photovoltaic and small-scale wind turbines, brings about new challenges to distribution system operators. DERs, such as VRE sources, battery energy storage systems, distributed (conventional) generators, and responsive loads, increase the complexity of the distribution system. Therefore, system characteristics shift away from the previously passive system toward an active distribution system. With an active distribution system, there comes a need for fair and transparent pricing schemes, which reward DERs for reducing losses, voltage violations, congestion, and imbalance of lines. Further, increased energy storage capabilities and demand-responsive loads will help integrate the distributed resources by instantaneously balancing generation and demand. These balancing actions must also be rewarded. Therefore, a distribution locational marginal price (DLMP) mechanism serving as a price signal for the economic dispatch of generation sources within the distribution system is first proposed. Defined as the marginal cost to supply the next increment of power to a specific location, this mechanism may encourage the acceptance of DERs due to the incentives arising from nodal pricing. DLMP components for energy, loss, voltage violation, and congestion for a linear approximation of the alternating current optimal power flow are leveraged in this work. The proposed method also addresses VRE uncertainty using the data-driven probability efficient point method. Numerical results show the DLMP mechanism can serve as a tool to improve distribution grid conditions by encouraging or discouraging real and reactive power consumption at specific nodes in the system. It is also demonstrated that three-phase real and reactive nodal pricing allows for better control of diverse DERs in active distribution systems. The DLMP is further used in a home energy management system application that utilizes the blockchain for secure communication. Next, an investigation into the impact of coupling the electricity distribution and drinking water networks on the DLMP and efficient VRE integration is undergone. Water pumps serve as demand-responsive loads that follow the available VRE generation. This technique is achieved by using elevated water tanks to optimally schedule the water network operation to meet water demands while improving grid conditions. A novel linear coordinated water and energy model is formulated and validated on a coupled electrical distribution system and water network. Results show the impact of coupling water and energy networks on the cost of operation and the DLMPs. The inclusion of water tanks as alternative storage devices in the electricity distribution network are shown to moderately reduce voltage violations, line congestion, and VRE curtailments in a case with high VRE penetration. Finally, unique demand response and storage solutions are identified within an agricultural community microgrid that considers an electricity-run green ammonia synthesis plant. The small-scale ammonia plant's operational schedule follows the available VRE generation to reduce VRE curtailment and improve grid conditions. Excess renewables in the system can be stored as chemical energy in anhydrous ammonia. When the price of electricity is extremely high, the proposed model accounts for a direct ammonia fuel cell that consumes ammonia to provide electricity back to the grid. This work proposes a linear coordinated operational model of an electricity distribution system and an electricity-run, green ammonia plant. Case studies are performed on an agricultural community microgrid. Results indicate the ammonia plant can adequately serve as a demand response resource and positively impact the DLMP. Studies showed this coupling decreased electricity costs of the ammonia plant by nearly a third, with ammonia profits increasing 17%. This dissertation can serve as a tool for utilities implementing the DLMP market mechanism in distribution systems. It can further assist with the operation of coordinated operation of water and electricity distribution networks under uncertain VRE generation. Finally, agricultural community microgrid operators can utilize techniques proposed in this dissertation with the hope of increasing the vitality of small towns and rural communities.
Keywords: Renewable energy integration; Food-energy-water nexus; Green ammonia plant; Distribution locational marginal price